Description of Using Video of Implementation of Posyandu as A Health Promotion Media During the Covid-19 Pandemic - Rinayati Rinayati; Novita Alfiani; Harsono Harsono (Indonesian Journal of Global Health Research, 2021)
With the new normal policy, in August 2020 In the yellow and green zones, posyandu activities have started to be implemented again, by implementing strict health protocols, the existence of socialization of the posyandu implementation carried out by cadres through social media and WA groups, the presence of mothers who has under five year children at posyandu is still not maximized at only 44%, there are still 56% of toddlers whose growth and development has not been monitored. there is a relationship between the level of parental knowledge and the visit to the posyandu in the new normal era, the delivery of messages or information requires the right media, one of the right media is video. This study aimed to knowing the Effectiveness of Using Video Implementation of the Posyandu During the Covid 19 Pandemic Against the Presence of Mothers has children under five years To Posyandu. Research subjects are mothers has children under five years in Gondoriyo village. Methods penelitian diskriptif. Measurements were carried out by pre-test and post-test, population 99 samples 53 using an observation instrument in the form of a checklist, data analysis using a frequency distribution. The percentage increase in the number of mothers who have toddlers before watching the video of the implementation of the posyandu during the covid 19 pandemic and after watching it increased by 9.9%. The video of the implementation of the posyandu during the pandemic was able to increase the presence of mothers at the posyandu.